2019
DOI: 10.4097/kja.d.18.00073.1
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium

Abstract: Delirium can be defined as "Acute Brain Dysfunction". Compared to dementia which is a disease that deteriorates the brain function in chronic course, delirium shows very similar symptoms but mostly ameliorates when the causative factors are normalized. Due to its heterogeneity of etiologies and symptoms, people including health care workers often mistake delirium for dementia or other psychiatric disorders. Delirium has attracted the global interest increasingly enough to gather vast amount of research on its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 87 publications
4
82
0
1
Order By: Relevance
“…Postoperative cognitive impairment (POD and POCD) is associated with high mortality and increased societal costs, which received increasing attention [1,[6][7][8]. Common concepts on the etiology are anesthesia-, surgery-, and patient-related factors [2,3,5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Postoperative cognitive impairment (POD and POCD) is associated with high mortality and increased societal costs, which received increasing attention [1,[6][7][8]. Common concepts on the etiology are anesthesia-, surgery-, and patient-related factors [2,3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Common concepts on the etiology are anesthesia-, surgery-, and patient-related factors [ 2 , 3 , 5 ]. Previous studies have reported that inflammation, neurotransmitter imbalance and sleep deprivation play an essential role in the pathogenesis of cognitive impairment [ 4 , 6 , 7 , 32 ]. Moreover, some studies indicated that intraoperative hypotension was linked to the development of POD or POCD [ 9 , 12 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Common concepts on the etiology are anesthesia-, surgery-, and patient-related factors [2,3,5]. Previous studies have reported that in ammation, neurotransmitter imbalance and sleep deprivation play an essential role in the pathogenesis of cognitive impairment [4,6,7,32]. Moreover, some studies indicated that intraoperative hypotension was linked to the development of POD or POCD [9,12,17].…”
Section: Discussionmentioning
confidence: 99%